Size-resolved hygroscopic behaviour and mixing state of submicron aerosols in a megacity of the Sichuan Basin during pollution and fireworks episodes. (1st April 2020) - Yuan, Liang; Zhang, Xiaoling; Feng, Miao; Liu, Xuan; Che, Yuzhang; Xu, Hanbing; Schaefer, Klaus; Wang, Shigong; Zhou, Yunjun
Abstract: In-situ measurements were carried out to study the size-resolved hygroscopic behaviour of submicron aerosols during pollution and fireworks episodes in winter from late January to February 2019 in Chengdu, a megacity in Sichuan Basin, using a hygroscopicity tandem differential mobility analyser (H-TDMA). The H-TDMA data were acquired at 90% relative humidity for dry aerosol diameters between 40 and 200 nm. Aerosol particles were usually externally mixed and consisted of nearly hydrophobic mode (NH), less hygroscopic mode (LH) and more hygroscopic mode (MH) in the urban area. The average ensemble mean hygroscopicity parameter values ( κ Mean ) over the entire sampling period were 0.16, 0.19, 0.21, 0.23 and 0.26 for aerosols with diameters of 40, 80, 110, 150 and 200 nm, respectively. These averages were lower than those in Shanghai and Nanjing. κ Mean for aerosols larger than 110 nm, however, were higher than those in Beijing and Guangzhou during winter. Distinct diurnal patterns for all measured sizes were observed for aerosol hygroscopicity and mixing state because of the photochemical reactions and the activities of the planetary boundary layer (PBL). The number fractions of the NH ( NF NH ) was low, but κ Mean was high, and more aerosols were internally mixed during daytime. The number fraction of LH ( NF LH ) for the 40-nm diameter aerosols in clean periods (CPs) was larger than that in the pollution episodes (PEs) because of the increasing amount of SOA formation. More aerosols of diameters larger than 80 nm were internally mixed during CPs and pollution accumulation period, resulting in higher κ Mean values. More strong hygroscopic components of fireworks were found in the larger aerosols during the fireworks episode (FE). The average κ Mean values of 0.19, 0.19, 0.21, 0.23 and 0.27 for the 40, 80, 110, 150 and 200-nm diameter aerosols, respectively, during the FE were higher than those during the pre- and post-FE periods. The findings of this study contribute to the preliminary understanding of the hygroscopic behaviour of urban aerosol particles in the Sichuan Basin, which are essential for understanding the formation and evolution of severe haze events in the Sichuan Basin. Highlights: H-TDMA measurements was carried out in a megacity of the Sichuan Basin. The hygroscopicity ( κ ) was higher than that in Beijing and Guangzhou during winter. κ during the fireworks episodes were higher than those in the rest of the campaign.